Alfalfa and alfalfa-grass mixture management - Mcdonald, Iryna (Kansas State University, 2018)
Alfalfa is an important forage legume grown in the central Great Plains. However, producers still lack information about the productivity of alfalfa grown with cool-season grasses and the proper time of the last cut of alfalfa in the fall. Two studies are presented in this dissertation. The first study was to determine during a three-year period (2015-2017) the dry matter yield (DMY) and forage nutritive value of alfalfa-grass mixtures compared to alfalfa and grasses grown in monoculture and to assess the effect of nitrogen fertilizer on the dry matter yield and nutritive value of alfalfa-grass mixtures. During the three-years, the DMY was significantly higher in monoculture alfalfa and alfalfa-grass mixtures than in grass monocultures. No significant differences in DMY between alfalfa monoculture and alfalfa-grass mixtures were found. For all treatments, nitrogen application significantly increased DMY compared to the control. In 2016 and 2017, acid detergent fiber (ADF) and neutral detergent fiber (NDF) in smooth bromegrass and tall fescue were higher than in other treatments. Nitrogen fertilizer application did not affect nutritive values such as crude protein (CP), ADF, NDF, and relative feed value (RFV) in different treatments of the forage species. The second study determined the effect of timing of a fall cut on dry matter yield, nutritive value, and stand persistence of alfalfa in Northeastern Kansas in the United States. The DMY of first cut in 2016 was significantly higher in the Roundup Ready variety of alfalfa than in the low-lignin variety of alfalfa. There were no significant differences in DMY between alfalfa varieties in the remaining seasonal cuttings in 2016 and 2017 and in the annual total yield in both years. The DMY of the last cut in the fall was the highest in 2015, 2016 and 2017 in plots that were harvested on September 30. In 2017 the highest DMY in first cut was found in plots that were cut on October 15 in the previous year. The last harvests of the 2016 season, which were on October 15 and October 30, had the highest nutritive value. Opposite results on October 15 and October 30 were observed in 2017. Alfalfa cut on September 15 and September 30 had a higher stand persistence compared to alfalfa cut on October 15 and October 30. In conclusion, last fall cutting of alfalfa, which could be up to October 15, appeared to be acceptable because it did not affect forage dry matter yield.
Keywords: Alfalfa; forage; management; nutritive value